Fungsi Legislasi DPRD Kabupaten Paluta Dalam Penetapan PERDA APBD Kabupaten Paluta - Sahbana Iwan Hasibuan (Inovasi Pratama Internasional. Ltd, 2022)
APBD is a regional financial management plan that is determined every year, approved by the Regional Government and DPRD and stipulated by a Regional Regulation. The APBD is a guideline for the Regional Government in carrying out regional revenues and expenditures. The formulation of the problem in this study is how the position and function of the DPRD of North Padang Lawas Regency in determining the Regional Regulation on APBD, implementation and obstacles in the legislative function of the DPRD of PALUTA Regency in determining the Regional Regulation of the Regional Budget of PALUTA Regency. This study uses a descriptive method through a normative approach (legal research) to obtain secondary data. The position and function of the Paluta Regency DPRD in the stipulation of the Regional Regulation on the APBD is as an element of the organizer of the PALUTA Regency Government. The DPRD is domiciled parallel to the Regional Government, can form a Regency Perda together with the Regional Head then discuss and give approval to the draft regional regulation regarding the Regency APBD submitted by the Regional Head of the PALUTA Regency. Barriers to the Legislation Function of the PALUTA Regency DPRD In setting the Regional Budget, the quality factor of the human resources of the PALUTA Regency DPRD members who have different educational backgrounds is that some are qualified and some are not. Less than optimal involvement of the community/stakeholders in the process of drafting and forming Regional Budgets. Suboptimal socialization and publications, both in the process of preparation and preparation, at the level of the institutions forming Regional Regulations, as well as after being ratified and promulgated for implementation. The last obstacle is that the process of forming a regional regulation must consider many factors, frictions, and interested parties are involved in making the process of drafting a regional regulation take longer.